Copper, Cadmium, chromium, nickel and lead in fishpond sediments. - Santillan, Jaina B.
The concentrations of nickel, cadmium, chromium, copper and lead were investigated in fishpond sediments collected fromUPV-CFOS-IA, Brackishwater Aquaculture Center. Total lead, nickel and copper concentrations of sediment samples are within the normal concentration in soils, while the total cadmium content exceeded the normal cadmium concentration in soils. The readily available/water soluble nickel, chromium, cadmium and copper in sediment samples are low except for lead, since most metals are bound to resistant phases than hinders them to become mobile in the environment. Salinity, pH and organic matter content of sediment samples are directly correlated to solubility of emtals in water. Regular monitoring of heavy metals on fishpond water and sediments are recommended to avoid possible detrimental effects of these metals to teh cultured organisms in the fishpond.